Någon särskild ansökan behöver inte göras – Opersonliga konstruktioner i myndighetstexter på svenska och finska i Finland och Sverige - Eveliina Tolvanen (Föreningen för nordisk filologi, 2022)
Impersonal  constructions  in  pension  authorities’  texts  in  Swedish  and  Finnish  in
Finland and Sweden
The  focus  of  this  study  lies  on  the  use  of  impersonal  constructions  that  have  an indirect  reference  to  either  the  writer  or  the  reader  of  the  text  in  institutional  texts about pensions.  The studied constructions  include passive without agent, nominalizations,  infinite  verb  constructions  and  constructions  with  the  pronoun  man  ‘one’  in Swedish,  and constructions with so-called zero person in Finnish.  The data includes four  groups  of  texts:  texts  published  in  Swedish  and  Finnish  in  Finland  and  texts published in Swedish and Finnish in Sweden.  The texts have been  published by Kela, the social security institution in Finland, and Pensionsmyndigheten, the  Swedish Pensions Agency, in  2012.  The theoretical  framework for the study consists of systemic-functional  linguistics  (SFL,  mainly  Halliday  &  Matthiessen  2004,  Thompson  &
Thetela 1995, Thompson 2003).
The  impersonal constructions in the data  are analyzed with regard to  who they refer to.  The results show that  impersonal  passive  constructions  tend to refer to the  writer, i.e.  the  pensions  authority  in  question,  whereas  infinite  verb  constructions,  the  pronoun  man  and zero person typically refer to the reader. Furthermore, impersonal constructions have both ideational, textual and interpersonal functions in the texts.
Keywords:  Swedish,  Finnish,  Finland-Swedish,  Sweden-Finnish,  impersonality, institutional communication, comparative analysis, SFL